PENINGKATAN MUTU DAN DAYA SIMPAN PASTA TOMAT DENGAN CARA BLANSING - Dewayani, Wanti; Darmawidah, Andi (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
The Increasing the Quality and Storage Period of Tomato Paste with Blanching Method. Up to the moment, the need of food industry for tomato paste is fulfilled by imported products. Processing raw tomato into tomato paste is one technique that will decrease the import dependency and increase the value added of the tomatoes. The aim of this research was to identify the quality of tomato paste by blanching treatments and the length of storage period. The experiment was arranged in randomized complete block design with two factors. The first factor was blanching treatments before the tomato is processed into tomato paste through four treatments; a) without blanching b) blanching within10 minutes, c) blanching within 20 minutes, and d) blanching within 30 minutes. The second factor was storage period which is divided into four periods i.e. 0, 1, 2 and 3 months. Parameter of quality which was observed was chemical quality (Vitamin C, sugar content, TPT and total acid) and organoleptic characteristics (color, texture, flavor and fondness). The result showed that oval variety can be processed into tomato paste and can be kept for a long time as recommended. However, the best tomato paste was obtained when blanched for 20 minutes and can be stored for 3 months. This tomato paste contained vitamin C 6.075 mg/100 g, sugar level 0.0085% and total acid 0.55%, total soluble solution 27Â°Brix, in red bright color 80%, aromatic and normal taste and be fond of. Based on fmancial analysis it was known that the farmers can process 200 kg fresh tomatoes into 100 kg tomato paste with profit rate amounting to Rp.1,860,000 with an R/C2.6. Key words: Blanching, processing, storage, tomato paste Selama ini kebutuhan industri pangan di Indonesia akan pasta tomat dipenuhi dari impor. Pengolahan tomat menjadi pasta akan memberi nilai tambah dan mengurangi ketergantungan impor. Tujuan penelitian ini adalah untuk mengetahui mutu pasta tomat yang dihasilkan dan perlakuan blansing dan lama simpan. Percobaan ini dilakukan dengan metode rancangan acak lengkap (RAL) pola faktorial. Faktor pertama adalah perlakuan blansing sebelum diolah menjadi saus tomat (4 taraf) yaitu tanpa blansing, blansing selama 10 menit, blansing 20 menit dan blansing 30 menit. Faktor kedua adalah perlakuan lama penyimpanan (4 taraf) yaitu 0, 1, 2 dan 3 bulan. Parameter mutu yang diamati adalah mutu kimia (vitamin C, kadar gula, TPT dan total asam) dan organoleptik (warna, tekstur, aroma, rasa dan kegemaran). Hasil penelitian menunjukkan bahwa varietas Oval dapat dibuat pasta dengan perlakuan blansing dan dapat disimpan lama sesuai dengan spesifikasi produk pasta tomat yang dipersyaratkan. Pasta tomat yang terbaik adalah yang diblansing 20 menit dan dapat disimpan 3 bulan. Pasta tomat tersebut mempunyai kandungan vitamin C 6,075 mg/100 g contoh, kadar gula 0,0085 %, total asam 0,55%, TPT 27 Â°Brix, wawa merah cerah 80%, aroma dan rasa normal serta digemari. Berdasarkan hasil analisis fmansial diketahui bahwa kelompok wanita tani dapat mengolah 200 kg tomat segar menjadi 100 kg pasta tomat dengan keuntungan sebesar Rp.1.860.000 dengan nilai R/C 2,6. Kata kunci : Blansing, penyimpanan, pasta tomat, pengolahan